U ODBRANU NEIZVESNOSTI: DOBRE STRANE NEODREĐENIH PRAVILA MEĐUNARODNOG PRAVA - Papić, Tatjana (Pravni zapisi, 2021)
The paper discusses uncertainty in international law from the perspective of its indeterminate rules against an often held view that such rules are bad news for international law. First, it shows that indeterminate rules are not a pathology, but inevitable in international law due to the diversity of states, their different interests, as well as complexities of some of the issues those norms attempt to regulate. Second, the paper claims that there is an upside in indeterminate rules if international law is conceptualized through its argumentative side. These values are explained through concrete examples of indeterminate provisions from the Treaty on the Non-proliferation of Nuclear Weapons and the UNSC Resolution 2249, a classical example of “constructively ambiguous” text. Relying on the works of Waldron and Hakimi, the paper explains how indeterminate rules accommodate disagreements, and consequently provide at least minimal regulation of certain contested issues, sustain international community, and, moreover, demonstrate how international law operates.